Pemanfaatan Situs Sejarah Candi Penataran sebagai Sumber Pembelajaran si Kelas 10 pada MA Assalam Jambewangi Selopuro-Blitar - Moh. Trio Fajar Subqi; Dita Hendriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research was motivated by the lack of enthusiasm of class X MA Assalam Jambewangi Selopuro Blitar students in learning history. History learning is carried out in the classroom in a conventional way which seems monotonous and boring. This greatly affects students' way of thinking, creativity and understanding of the material and has an impact on learning outcomes that are less than optimal, therefore it is necessary to innovate learning methods so that the idea emerged from researchers to research the use of Penataran Temple as a source of historical learning. The problem formula in writing this inscription is 1. What are the steps for learning history, 2. What are the supporting and inhibiting factors, and 3. What are the implications of implementing history learning (by using the Penataran Temple Site as a source of history learning by applying to class X MA students Greetings). This research aims to find out the steps for learning history, what are the supporting and inhibiting factors, and what are the implications of implementing the use of the Penataran Temple Site as a source of history learning by applying the inquiry method to class X MA Assalam students. This research is a descriptive qualitative type of research with data collection techniques through observation, in-depth interviews and documentation.